Ovisidal dan Vermisidal Bawang Putih (Allium Sativum) Terhadap Cacing Ascaridia Galli Pada Ayam Buras: Penelitian Eksperimental Laboratoris - Ida Bagus Made Oka, - (2001)
A study has been carried out to assess the ovicidal and vermicidal action of garlic on egg and adult helminth of A. galli in local chickens. A completely randomized design was applied with treatments with garlic in dose of 2 g (P2), 3 g (P3), 4 g (P4), 5 g (Ps), 6 g (P6) respectively, and com (Po as control). Each treatment was replicated 8 times. Assessment of the ovicidal effect of garlic, both directly and indirectly, on A. galli eggs was done on day 10,15 and 25. To compere the ovicidal result of garlic with direct contact and indirect effect a statistical analysis of independent t test was done. Vermicidal effect of garlic on A. galli adult worms was observed 7 days after treatment. The result showed that direct contact of garlic with A. galli egg on day 10, 15 and 25 gave an ovicidal effect significantly greater than control (P<0,05). The ovicidal effect increased with dose increase except for P 5 and P 6 whose effec was not significant (P>0,05). Indirect ovicidal effect of garlic on day 10, 15 and 25 showed insignificantly different effect between Po and P2 (P>0,05). The direct contact ovicidal effect of garlic on A. galli eggs was significantly better than the indirect effect in all types of dose treatment (P<0,05). The vermicidal effect of garlic on A. galli adult worms was significantly different than the control (P<0,05). The vermicidal effect increased significantly with increase of dose.